Production of Bio Degradable Bags Using cassava Starch - S, Sharmiladevi; N, Ramesh; S, Ramesh (International Research Journal of Multidisciplinary Technovation, 2019)
Plastic is a material that is used to a great extent. Nowadays Petroleum based plastics are widely used for the commercial purpose. This kind of plastics can take more than a century to degrade. Man made plastics have Polyurethane and Polyethylene polymers. It cannot be easily degraded by micro organisms as it don’t recognize as food. When burned plastics release cancer causing carcinogenic chemicals that are harmful to people and the environment. One eco friendly alternative the current commercial plastic is “Bio plastics”. Bio plastics are biodegradable plastics that have components derived directly from renewable raw plant materials. Seven type of bioplastics were made using various combinations of renewable raw materials and plasticizers. In this project, Cassava starch is used as a main biopolymer for the production of bio degradable bags.